Developing multilayer microfluidic platforms and advancing laser induced fluorescent detection and electrochemical detection to analyze intracellular protein kinases, reactive nitrogen and oxygen species in single cells - Patabadige, Damith Randika E.W. (Kansas State University, 2017)
Recent approaches in analytical separations are being advanced towards the “lab-on-a-chip” concept in which multiple lab functions are integrated into micro/nano fluidic platforms. Among the variety of separation techniques that can be implemented on microfluidic devices, capillary electrophoresis is the most popular as it provides high efficiency, simple, fast and low cost separations. In addition, integrating miniaturized fluid manipulation tools into microfluidic devices with separations is essential for a variety of biological applications. Chapter 1 discusses the fundamentals of capillary electrophoresis and miniaturized fluid manipulation tools and provides an over view of single cell analysis in microfluidics. In chapter 2, the integration of miniaturized peristaltic pumps into multilayer microfluidic platforms is discussed. In addition, device characterization, precise fluid control and high throughput single cell analysis are discussed. As a proof of principle, T-lymphocytes were loaded with two fluorescent probes Carboxyfluorescein diacetate (CFDA) and Oregon green (OG). Thousands of single cells were automatically transported, lysed on these devices and analytes from the lysate were electrophoretically separated. 1120 cells were analyzed over the course of 80 min (14 cells/min) and separation characteristics of analytes released from individual cells were investigated. In the third chapter, the development of microfluidic platforms for the electrochemical detection of nitric oxide (NO) and other reactive nitrogen species (RNS) at the single cell level is discussed. A microfluidic system was developed to perform rapid cell lysis followed by electrochemical detection. Miniaturized microband electrodes were designed and integrated with a microfluidic separation channel. Three alignment techniques (in-channel, end-channel and off-channel configurations) were used to detect the electrochemical response of the analyte of interest. Furthermore, a model analyte (CFDA) was used to demonstrate the potential of performing the simultaneous dual detection with electrochemical and laser induced fluorescence detection. In addition, the same microfluidic platform was adapted to detect intracellular superoxide using laser induced fluorescence. In the fourth chapter, the off-chip integration of optical fiber bridges with multilayer microfluidic chips is discussed. A multimode optical fiber (~10cm long) was integrated between the single cell lysing spot and a spot downstream of the separation channel in order to detect both intact cells and the analyte in the lysate. This technique was used to create two detection spots on the microfluidic platform with the use of a single excitation source and single detector. Fluorescently labeled T-lymphocytes were automatically transported and lysed in a manner similar to that described in chapter 2. Hundreds of single cells were analyzed and the absolute migration time was determined for the analytes in the lysate. In addition, the separation characteristics of fluorescently labeled protein kinase B peptide substrates were investigated. Furthermore, this technique was used to measure cell size and the velocity of intact cells (discussed in 5th chapter) by making use of a light tunneling concept available in multimode optical fibers. All the experiments presented in this dissertation exploit the use of multilayer microfluidic platforms to investigate intracellular components in single cells in a high throughput manner that has several advantages over current conventional techniques.
Keywords: Micropumps; Fiber optics; Single cell analysis; Softlithography; Laser induced fluorescent detection and electrochemical detection; Multilayer microfluidic devices